Genetic effects of season on the preweaning growth of beef cattle: a first approach to Retinta calves - Morales, Rosa M.; Menéndez-Buxadera, Alberto; Demyda-Peyrás, Sebastián; Molina, Antonio (Revista Colombiana de Ciencias Pecuarias, 2019)
Background: Heat stress derived from global warming is causing major economic losses in the livestock industry. Objective: To develop a novel methodological approach for determining the influence of climatic factors on the estimation of genetic parameters for growth traits in Retinta cattle breed by using reaction-norm models. Methods: Live weight records (n=7,753) from 3,162 Retinta calves born from 1,249 dams and 85 sires and raised in the Andalusian region (Spain) were analyzed. The effect of heat stress was measured using the temperature-humidity index, calculated with climatological data obtained from four weather stations. A bivariate-random-regression reaction-norm model was used to estimate the (co)variance components of weight until weaning in two different climatic seasons corresponding to warm and cold months. Results: The heritability pattern of individuals reared under diverse environments during the first 90 days of age was different. However, differences were not significant at the end of the growing period. Weaned calves reared during the cold season showed greater growth from 70 to 160 days in comparison with those reared during the warm season. Conclusions: Highly significant evidence of genotype-climatic condition interaction was found during the calf´s first three months of growth.